2023
DOI: 10.1097/sap.0000000000003494
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Distribution Patterns in Early-Stage Upper Extremity Lymphedema

Abstract: Introduction Magnetic resonance imaging (MRI) stage 1 (early stage) upper extremity lymphedema is characterized by fluid infiltration in the subcutaneous tissues that does not exceed 50% of the extremity circumference at any level. The spatial fluid distribution in these cases has not been detailed and may be important to help determine the presence and location of compensatory lymphatic channels. The aim of this study is to determine whether there was a pattern of distribution of fluid infiltratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that lymphedema does not affect the limb uniformly [ 15 ]. Friedman et al demonstrated that lymphedema of the forearm predominantly distributed in the ulnar aspect followed by the volar aspect [ 20 ]. Within the upper arm, the majority of the fluid infiltration was seen distally and posteriorly [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that lymphedema does not affect the limb uniformly [ 15 ]. Friedman et al demonstrated that lymphedema of the forearm predominantly distributed in the ulnar aspect followed by the volar aspect [ 20 ]. Within the upper arm, the majority of the fluid infiltration was seen distally and posteriorly [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Friedman et al demonstrated that lymphedema of the forearm predominantly distributed in the ulnar aspect followed by the volar aspect [ 20 ]. Within the upper arm, the majority of the fluid infiltration was seen distally and posteriorly [ 20 ]. This was corroborated by our results, as there was a similar distribution in maximal dermal thickening.…”
Section: Discussionmentioning
confidence: 99%